Virus-First Theory Revisited: Bridging RNP-World and Cellular Life - Francisco Prosdocimi; Savio Torres de Farias (Microbiology Research)
The virus-first theory presents a model in which viral lineages emerged before cells. This proposal aims to give the theory greater relevance by offering a plausible evolutionary framework that explains both (i) the origin of viruses from prebiotic chemistry and (ii) how viruses contributed to the emergence of cells. Here, we propose that viruses should be understood as a distinct class of ribonucleoprotein (RNP) systems, some of which evolved directly from the RNP-world. In our model, simple progenotes produced capsid-like particles through the evolution of a single gene encoding a self-assembling peptide. This allowed the formation of icosahedral shells around RNA genomes, as observed today in certain viral families whose capsids consist of ~60 identical subunits derived from a single gene product. These early capsids enabled mobility and protection, representing key intermediates toward biological complexity. Over time, some of those populations acquired additional peptides and evolved more elaborate architectures. Finally, the incorporation of lipid-binding domains in those capsid-like peptides allowed the formation of proteolipidic membranes akin to those found in modern cells. This model provides a gradualistic and logically coherent evolutionary path from the RNP-world to the emergence of cellular life, emphasizing the foundational role of viruses in early evolution.